Analytical and digital photogrammetric geodata production systems (a comparison test) - Ruzgienė, Birutė; Aleknienė, Edita (Geodesy and Cartography, 2012)
Up‐to‐date mapping technologies are in the middle of transition from analytical to digital. The usage of new methods and technologies implies the desire to increase mapping capability. Despite that, analytical and digital methods may be used simultaneously, thus getting more efficient results. The research objective is to present some aspects of functionality of both digital and analytical photogrammetric mapping approaches in generating 3D geodata. The experimental results show which of the two methods could lead to a more flexible mapping production in consideration of the following criteria: accuracy, flexibility, time and cost. The main result of investigations shows, that the orthophoto generation is successfully using fully automatic systems. The digital terrain models created by two technologies are almost the same due to time‐consuming. Therefore more time is required for the Digital Photogrammetric System when the terrain is rougher. Despite the fact that digital photogrammetric mapping technology drastically develops, there is no doubt that analytical photogrammetry is still a significant production system for large‐scale mapping. The results demonstrate that there is not too much difference in accuracy between the analytical and the digital 14 μm pixel size images processing. The interpretation capability of experimental test area in the Digital Photogrammetric System was more complicated as it was by the analytical plotter. Two systems integrations have been foreseen. Digital terrain model obtained by the analytical plotter can be transferred to digital mapping system for orthophoto generation.First published online: 03 Aug 2012